IMPLEMENTATION OF POLITICAL EDUCATION AT PONDOK PESANTREN NIHAYATUL AMAL IN FORM POLITICAL LITERACY OF SANTRI TO CREAT POLITICAL CULTURE OF PANCASILA - Silvia Sofyan, Fitri; Riswandi Sanusi, Aris; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
Political education is a means of education of citizens aimed at creating a political literate citizen and able to behave in a responsible political and based on the noble values of Pancasila. Pupils are an integral part in the political life of the state has an important role to be actively involved in any act of the state’s political behavior. Shallow outlook on the role of students in the political life of Indonesia, making political education as an obligation that must be held for students have a political understanding based on the values of religious and cultural values of the nation which has been formulated in a national ideology of Pancasila